Welfare Indicators for farmed Atlantic salmon : tools for assessing fish welfare - Noble, Christopher; Gismervik, Kristine; Iversen, Martin Haugmo; Kolarevic, Jelena; Nilsson, Jonatan; Stien, Lars Helge; Turnbull, James F. (Nofima, 2018)
publishedVersion